2011
DOI: 10.1016/j.ridd.2011.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, anxiety and challenging behaviour in children with intellectual disability and/or autism spectrum disorder

Abstract: Children with an intellectual disability (ID) and/or autism spectrum disorder (ASD) are known to suffer from significantly more sleep problems, anxiety and challenging behaviour (CB) than typically developing children (TD), yet little is known about the relationship between these factors in the child ID/ASD population. The study aim was to examine these relationships. We hypothesised that there would be significant positive correlations between the three factors and that sleep problems and anxiety would predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
75
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 64 publications
10
75
3
Order By: Relevance
“…In addition, visual analyses suggested that a data path representing rate of problem behavior following nights with low sleep was not differentiated from a data path representing rate of problem behavior following nights with average sleep. Our findings are contradictory to the majority of previous research in this area, which has suggested that sleep and problem behavior are related (Mazurek et al 2013;Rzepecka et al 2011) and that low sleep leads to increased problem behavior (Kennedy and Meyer 1996;O'Reilly 1995).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, visual analyses suggested that a data path representing rate of problem behavior following nights with low sleep was not differentiated from a data path representing rate of problem behavior following nights with average sleep. Our findings are contradictory to the majority of previous research in this area, which has suggested that sleep and problem behavior are related (Mazurek et al 2013;Rzepecka et al 2011) and that low sleep leads to increased problem behavior (Kennedy and Meyer 1996;O'Reilly 1995).…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies using parental report indicate that children with problem behavior are also more likely to have sleep difficulties (e.g., Mazurek et al 2013;Rzepecka et al 2011), while others suggest that the two domains are not correlated (Dominick et al 2007). There has also been support from a direct observation study suggesting that individuals who exhibit problem behavior have more sleep difficulties when compared to national norms (Piazza et al 1996), but these findings are correlational in nature and do not provide information about a temporal relationship.…”
mentioning
confidence: 99%
“…They may also experience co-morbid conditions that can make differential diagnosis difficult, such as Autism Spectrum Disorder (Croen et al, 2002), as well as increased levels of mental health problems, challenging behaviour and sleep disturbances (e.g. see Rzpecka et al, 2011). Early diagnosis of ID is crucial to ensure that the child receives appropriate support and intervention to maximise his/her life chances (Guralnick, 2005), however research suggests that diagnosis can often be delayed, into adolescence or even adulthood (Hamilton, 2006) and that this can be a significant source of stress and dissatisfaction for parents (Watson et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Research does, however, suggest common difficulties that are shared by many people with an intellectual disability (Emerson, Hatton, Bromley, & Caine, 1998), including with working memory (Schuchardt, Gebhardt, & MĂ€ehler, 2010) and understanding more abstract concepts such as time (Owen & Wilson, 2006). As a result, many children with an intellectual disability may require some additional support in relation to areas such as education (Simonoff et al, 2006), relationships (Heiman, 2000) and behaviour (Rzepecka, McKenzie, McClure, & Murphy, 2011). The family may also require support, as research suggests that having a child with an intellectual disability can impact on the family unit.…”
Section: Introductionmentioning
confidence: 99%